PROFIL LKS MATERI PERUBAHAN LINGKUNGAN BERORIENTASI KURIKULUM 2013 UNTUK MELATIHKAN BERPIKIR KRITIS SISWA - PUSPITADEWI, SEPTIANA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The porpose of this research describes the feasibility of Development Student Worksheet Topic Environmental Changes Oriented Curriculum 2013 for Practice Critical Thinking Students theoretically. Type of this research is a development research refers to the 4-D, but in this research disseminate step didn’t held. The subjects of this research were 20 students of class X-MS in SMAN 1 Boyolangu, Tulungagung. The parameters measured in this research include that, theoretically LKS feasibility assessment by three validator. Student worksheet theoretical assessment consists of aspects of the content, presentation, and language. Data analysis was performed quantitative descriptive. The results of this research indicate that the feasibility of student worksheet theoretically has known through the results of the validation with score of 96,5% with very decent criteria. Key words: student worksheet development, environmental material chage, curriculun 2013, critical thinking.